Nigella sativa oil alleviates ultrastructural alterations induced by tramadol in rat motor cerebral cortex. Issue 2 (June 2016) - Omar, Nesreen Moustafa
Abstract: Tramadol is an opioid analgesic used to alleviate acute and chronic pain. Nigella sativa oil is one of the traditional remedies with antioxidant activity. This study was designed in order to investigate the ultrastructural alterations induced by tramadol in the rat cerebral cortex and to find out any possible protective effect of N. sativa oil against these alterations. Twenty-four male albino rats were assigned to three groups. Group I received intraperitoneal and oral normal saline for 30 days. Group II received intraperitoneal injections of tramadol 20 mg/kg/day, 40 mg/kg/day and 80 mg/kg/day on the first, second and third 10 days of the study, respectively. Group III received intraperitoneal tramadol similar to Group II and oral N. sativa oil at a dose of 4 ml/kg/day for 30 days. Specimens from the motor area were obtained and processed for transmission electron microscopy. In the tramadol-treated group, pyramidal and granular cells appeared shrunken and showed ultrastructural features of apoptosis such as nuclear membrane invaginations, chromatin margination, dilated rough endoplasmic reticulum, dilated Golgi saccules, and mitochondria with disintegrated cristae. The myelinated axons showed disorganization and splitting of the myelin sheath and contained vacuoles and abnormal mitochondria. Administration of N. sativa oil partially protected the cortical neurons and myelinated axons against tramadol-induced changes. In conclusion, N. sativa oil alleviates ultrastructural apoptotic changes induced by tramadol in the rat motor cerebral cortex.